2015
DOI: 10.1021/acsami.5b07883
|View full text |Cite
|
Sign up to set email alerts
|

Soy Protein Isolate As Fluid Loss Additive in Bentonite–Water-Based Drilling Fluids

Abstract: Wellbore instability and formation collapse caused by lost circulation are vital issues during well excavation in the oil industry. This study reports the novel utilization of soy protein isolate (SPI) as fluid loss additive in bentonite-water based drilling fluids (BT-WDFs) and describes how its particle size and concentration influence on the filtration property of SPI/BT-WDFs. It was found that high pressure homogenization (HPH)-treated SPI had superior filtration property over that of native SPI due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 51 publications
0
63
0
Order By: Relevance
“…Li et al [47] studied the utilization of a commercially available soy protein isolate (SPI) as fluid loss additive in bentonite-water based drilling fluids (BT-WDFs). The results indicated that at low SPI concentrations (0.5, 1.0, 1.5 wt %), strong aggregations were formed, resulting in the formation of thick, high-porosity and high-permeability filter cakes giving high fluid loss values.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Li et al [47] studied the utilization of a commercially available soy protein isolate (SPI) as fluid loss additive in bentonite-water based drilling fluids (BT-WDFs). The results indicated that at low SPI concentrations (0.5, 1.0, 1.5 wt %), strong aggregations were formed, resulting in the formation of thick, high-porosity and high-permeability filter cakes giving high fluid loss values.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Sodium-bentonite contains 70–90 wt.% sodium-Mt and it has a high swelling capacity. Potassium ions are often used in these types of drilling formulations owing to their roles as swelling inhibitors (Li et al , 2015; Barast et al , 2017). The second type is the sepiolite/palygorskite (Pal) group (Wang & Wang, 2016).…”
mentioning
confidence: 99%
“…as fluid loss agents are also widely mentioned in recent studies. For example, Li et al added soybean isolation (6 wt%) into drilling fluid and reduced the filtration rate from 7.5 mL/s to 2.5 mL/s due to the permeability decrease in filter cake [ 99 ]. Through another mechanism, the function of rice husk as fluid loss agents lies in its ability to increase the thickness of filter cake [ 100 ].…”
Section: Application Of Polysaccharide Biopolymer In Petroleum Recmentioning
confidence: 99%